Automated detection of remineralization in simulated enamel lesions with PS-OCT - Lee, Robert C. (2014)
Previous in vitro and in vivo studies have demonstrated that polarization-sensitive optical coherence tomography (PS-OCT) can be used to nondestructively image the subsurface structure and measure the thickness of the highly mineralized transparent surface zone of caries lesions. There are structural differences between active lesions and arrested lesions, and the surface layer thickness may correlate with activity of the lesion. The purpose of this study was to develop a method that can be used to automatically detect and measure the thickness of the transparent surface layer in PS-OCT images. Automated methods of analysis were used to measure the thickness of the transparent layer and the depth of the bovine enamel lesions produced using simulated caries models that emulate demineralization in the mouth. The transparent layer thickness measured with PS-OCT correlated well with polarization light microscopy (PLM) measurements of all regions (r(2)=0.9213). This study demonstrates that PS-OCT can automatically detect and measure thickness of the transparent layer formed due to remineralization in simulated caries lesions.